Deletion of Miro1 in airway club cells potentiates allergic asthma phenotypes - Bruno, Sierra; Lamberty, Amelia; McCoy, Margaret; Mark, Zoe; Daphtary, Nirav; Aliyeva, Minara; Butnor, Kelly; Poynter, Matthew E.; Anathy, Vikas; Cunniff, Brian (Frontiers in Allergy, 2023)
Mitochondria are multifaceted organelles necessary for numerous cellular signaling and regulatory processes. Mitochondria are dynamic organelles, trafficked and anchored to subcellular sites depending upon the cellular and tissue requirements. Precise localization of mitochondria to apical and basolateral membranes in lung epithelial cells is important for key mitochondrial processes. Miro1 is an outer mitochondrial membrane GTPase that associates with adapter proteins and microtubule motors to promote intracellular movement of mitochondria. We show that deletion of Miro1 in lung epithelial cells leads to perinuclear clustering of mitochondria. However, the role of Miro1 in epithelial cell response to allergic insults remains unknown. We generated a conditional mouse model to delete Miro1 in Club Cell Secretory Protein (CCSP) positive lung epithelial cells to examine the potential roles of mitochondrial trafficking in the lung epithelial response to the allergen, house dust mite (HDM). Our data show that Miro1 suppresses epithelial induction and maintenance of the inflammatory response to allergen, as Miro1 deletion induces increases in pro-inflammatory signaling, tissue reorganization, and airway hyperresponsiveness. Furthermore, loss of Miro1 in CCSP+ lung epithelial cells blocks resolution of the asthmatic insult. This study further demonstrates the important contribution of mitochondrial dynamic processes to the airway epithelial allergen response and the pathophysiology of allergic asthma.